A coupled finite element-meshfree smoothed point interpolation method for nonlinear analysis. (1st July 2021) - Saliba, Samir Silva; Gori, Lapo; da Silva Pitangueira, Roque Luiz
Abstract: In this paper, coupling between the finite element method (FEM) and the smoothed point interpolation methods (SPIM) is employed in the study of inelastic problems where the meshfree methods presents attractive characteristics. These studies are based on a strategy whose inelastic region is previously discretised by a SPIM method, while the rest of domain is represented by FEM. Linear and nonlinear numerical simulations are presented, and the results of simulations are compared, when possible, to analytical solutions and experimental results in order to demonstrate the main features of the proposed coupling.